The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1182/blood-2002-04-1096
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppression induced by intratumor administration of adenovirus vector expressing NK4, a 4-kringle antagonist of hepatocyte growth factor, and naive dendritic cells

Abstract: NK4, a 4-kringle antagonist of hepatocyte growth factor (HGF), is a potent inhibitor of tumor angiogenesis and functions independently of its HGF-antagonistic activity. We have shown previously that in vivo genetic modification of tumors with an adenovirus vector that expresses NK4 (AdNK4) restrains tumor angiogenesis and slows the rate of tumor growth in vivo. In the present study, we investigated the hypothesis that this can be made more efficient by also administering bone marrow-generated dendritic cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 34 publications
0
46
1
Order By: Relevance
“…E.G7-OVA cells were grown in complete RPMI 1640 containing 0.4 mg/ml G418 (Invitrogen, Carlsbad, CA). Dendritic cells were generated from mouse bone marrow precursors as described previously (21)(22)(23). LLC cells were maintained in complete DMEM (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…E.G7-OVA cells were grown in complete RPMI 1640 containing 0.4 mg/ml G418 (Invitrogen, Carlsbad, CA). Dendritic cells were generated from mouse bone marrow precursors as described previously (21)(22)(23). LLC cells were maintained in complete DMEM (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that intratumoral injection of DCs induced antitumor effects. 33,34 In addition, HSP70-enhanced antigen uptake 19 and HSP70-induced DC maturation 20,21 have been reported. This indicates that injection of DCs directly into tumors releasing HSP70 after hyperthermia using magnetite nanoparticles is a possible approach for immune induction.…”
mentioning
confidence: 99%
“…IL-12 can promote the development of Th1 CD4 ϩ T cells, which facilitate maturation of CD8 ϩ CTLs whereas MIP-1␣ promotes CD8 ϩ T cell migration and their interaction with DCs. 37,38 Ad-mCD40L-activated A20 B cells are potent APCs as judged from the strong specific proliferative activity in an MLR. Infecting the cells with Ad-mIL-2, which resulted in mIL-2 production as a means to compensate for that normally produced during B7/CD28 interaction, had no effect on the surface phenotype of either MHC or costimulatory molecules.…”
Section: Discussionmentioning
confidence: 99%